Analytical study of the reality of cliques ABO incompatibility in newborns at AlYarmouk and Al-Kadhimiya teaching hospitals in Baghdad province: Mustafa A.K. Al-Taie; Jabbar H. Yenzeel Al-Hilfy and Nusaibah Amer - Al-Taie, Mustafa A.K. (The Iraqi Journal of Veterinary Medicine, 2013)
In this study blood samples were collected from 150 newborns (NBs), In a period from 20082010, with blood groups A and B from mother’s blood group O positive and those who do not have any other reason for the jaundice..Of 150 NBs, 105 have blood group A and 45 with group B. And the male to female ratio was 1.7:1. The average of NBs age at the onset of jaundice was 19.02 hrs, it was earlier in blood group B and in newborns of first pregnancy. The average of serum bilirubin level at 24 hours was 5.70 mg/dl; there was no statistical value of the blood group and the sex of the NBs in the bilirubin level. Newborns had anemia at delivery in 12 cases, 6 of them were premature. Fifty one NBs were followed for late anemia and found 36 (70%) had anemia. Comparing results between NBs who had anemia and those who had not, found that the bilirubin level was higher in anemic NBs, and they had longer stay in Hospital